Descriptive study on the implementation of teaching Reading to the tenth grade students of senior High school of assalaam Surakarta In 2012/2013 academic year - Pragoto, Akbar Hari Yudha; , Drs. Djoko Srijono, M.Hum; , Dr. Anam Sutopo, M.Hum (2014)
The objective of this study is to descriptive study on the implementation of the teaching reading to the tenth grade students of Senior High School of Assalaam Surakarta in 2012 / 2013 Academic Year. The writer focuses the study on some dimensions, they are: 1) Curriculum, including about Competence-Standard of English Lesson for SMA, Basic Competence, syllabus, and material, 2) Method of teaching, that consists of student's role and teacher's role, 3) Learning media, 4) Evaluation system, and 5) Environment. The last is the strengths and the weaknesses of the teaching reading skills implementation. In this study, the writer uses descriptive qualitative researchas the proper method to describe the implementation of the current curriculum in English teaching since the descriptive research aims at providing as accurately as possible of what current practice is; how learners do learn; how teachers do teach; what classroom looks like; at particular moment in particular place. This research called qualitative reseacrh because it was relying on the collection of qualitative data. The result of the observation in teaching learning process of English the writer finds that the process of teaching and learning is task-based instructions. The teacher gives more explanation, so the teacher becomes the counselor. There are three steps of teaching and learning activities, namely; opening, study session (the explanation), and closing, 2) To support this curriculum in the teaching learning process, the teacher uses some learning media, they are; flash card, internet, tape recorder, and television. Therefore, the writer concludes that the implementation of the material is still less, many examples of the material does not transfer maximally, 3) The writer finds that the students tend to be active in the class, when the teacher starts the teaching learning process, the students are just listening to the teacher's explanation about the material. Based on the research finding, there are strengths on the teaching reading. The first it had good procedural steps on teaching learning process. The second, the teacher applies an interesting system in order to attract the student's attention. And the weaknesses are the first, the teacher is more focus on the written form, then the teacher holds the remedial test for all of the students without any exception. So that the students get bored and not interested, that makes the students lazy to learn and participate. Hence, it is necessary that the teachers always rehearse how to manage themselves prior to teaching in the class.